PENGGUNAAN DIALEK MINANG PADA NOVEL TERUSIR KARYA BUYA HAMKA - Permana, Siti Nurisnie Fadillah; Juwita, Evi Ratna; Isnaini, Heri (IKIP Siliwangi, 2018)
The research to discuss about using dialect Minang Language. At novel Terusir by Buya Hamka wuth using theory linguistics dialektologis social as a descriptive methods. In a novel Terusir consiset a Minang dialect language in daily activity. In this case have interpretation with Indonesian language in term of gramatical and lexical. Source of research Minang language in a novel Terusir by Buya Hamka using technique list that is writen and compared with Indonesian language. Analysis techniques in a research make a simple to understand utilized interpretation of Minang language in Indonesian language. The result from the research be found the same words, between dialect Minang in novel Terusir with Indonesian language in daily activiy. The quanty of different words between dialect Minang and Indonesian language it 12% word the percentage of utilized dialect Minang at the novel Terusir get 60 % (precents) this case indicate the work indine a using Minang language the compare with Indonesian language. Althought this work is refresments by readers majority except Minang